The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1055/s-0035-1554632
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Insulin-like Growth Factor Binding Protein-3 Predicts One-year Outcome after Ischemic Stroke

Abstract: IGFBP-3 levels after ischemic stroke may independently predict functional outcome after one year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…The observed predictive value of low IGFBP-3 levels on outcome were also independent of IGF-1 levels, which have been connected to neurological outcome elsewhere [17,19,25]. Thus, it remains plausible to consider IGFBP-3 to be more than just a simple binding protein; it has autonomous neuroprotective effects [20]. IGFBP-3 might exert a key function on vasculogenesis and microvascular remodeling after hypoxic injury, similarly to effects of vascular endothelial growth factor, which has been demonstrated to optimize cerebral blood flow, decrease infarction size and preserve the metabolic penumbra after ischemic tissue damage [12,13,26].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The observed predictive value of low IGFBP-3 levels on outcome were also independent of IGF-1 levels, which have been connected to neurological outcome elsewhere [17,19,25]. Thus, it remains plausible to consider IGFBP-3 to be more than just a simple binding protein; it has autonomous neuroprotective effects [20]. IGFBP-3 might exert a key function on vasculogenesis and microvascular remodeling after hypoxic injury, similarly to effects of vascular endothelial growth factor, which has been demonstrated to optimize cerebral blood flow, decrease infarction size and preserve the metabolic penumbra after ischemic tissue damage [12,13,26].…”
Section: Discussionmentioning
confidence: 97%
“…Denti et al found no association between IGFBP-3 and outcome [19]. In contrast, murine and preliminary human studies point at a potential role of IGFBP-3 in acute ischemic stroke [18,20].…”
Section: Introductionmentioning
confidence: 99%
“…Further factors related to IGFs have been recently associated with stroke and may suggest emerging biomarkers in this pathology. A recent study showed that not only low levels of IGF-1 were associated with an unfavourable functional outcome of stroke but also the level of insulin-like growth factor binding protein-3 (IGFBP-3) [35]. More favourable outcomes should be yet associated with the evaluation of the decrease in the IGF-1 ratio and with IGFBP-3, rather than with serum levels of IGF-1 [150].…”
Section: Bone-skeletal Muscle Biomarkers In Strokementioning
confidence: 99%
“…There have been a number of studies that demonstrate the beneficial neuroprotective and neuroreparative effects of M2 switching [68][69][70][71]. These studies have focused on the importance of various M2 markers such as IL-4 [72,73], IL-10 [72,74,75], IL-1RA [76], TGF-β [77,78], CD206 [72,79], arginase 1 [79,80], granulocyte macrophage colony-stimulating factor [72], insulin-like growth factor 1 [81,82], and peroxisome proliferator-activated receptor-γ [70,71,83]. Even though our understanding of the role of these individual factors have become more insightful, it is very difficult to achieve beneficial neuroprotective effects by modulating just one of these factors.…”
Section: Targeting Microglia As a Therapeutic Strategymentioning
confidence: 99%